PENGARUH LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA DAN ORGANIZATONAL CITIZENSHIP BEHAVIOR - Syahriani Syahriani; Nurwati Nurwati; La Hatani Hatani (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2017)
The purposes of this study are to examine and to explain the effect of work environment on employee’s OCB that mediated by job satisfaction in the Civil Registration Service of Muna Regency. The approach of this research is explanatory research and data is collected cross-sectionally through the instrument of questionnaire. The population of this study is all civil servants in the Population and Civil Registration Service of Muna Regency with 28 employees as respondents. Analytical equipment used to test the hypothesis of this research is Partial Least Square (PLS).The results showed a partially significant effect of the work environment on job satisfaction, but the employee’s OCB has no significant effect. Then job satisfaction has a significant effect on employee’s OCB. Finally the results of this study indicate that job satisfaction acts as a perfect mediation (complete mediation) influence between the work environment and OCB employees. It means that a good work environment has a significant effect on the increasing of job satisfaction and job satisfaction has a significant effect on OCB, but the work environment has no directly significant effect to the increasing of employee’s OCB.Keywords: work environment, job satisfaction, organizational citizenship behavior